Nano Online 2016
DOI: 10.1515/nano.12951_2015.31
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the magnetic labeling of human neural stem cells and MRI visualization in the hemiparkinsonian rat brain

Abstract: Background: Magnetic resonance imaging is the ideal modality for non-invasive in vivo cell tracking allowing for longitudinal studies over time. Cells labeled with superparamagnetic iron oxide nanoparticles have been shown to induce sufficient contrast for in vivo magnetic resonance imaging enabling the in vivo analysis of the final location of the transplanted cells. For magnetic nanoparticles to be useful, a high internalization efficiency of the particles is required without compromising cell function, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 34 publications
(42 reference statements)
2
13
0
Order By: Relevance
“…We did not observe any substantial differences in differentiation potential between labeled and non-labeled cells. This is in agreement with previous results on the differentiation of labeled cells in human ventral mesencephalic cells, 31 human fetal midbrainderived neural precursor, 37 SPIO-labeled human neural stem cells 28 and human fetal neural precursor cells. 45 Similarly, in iPSC-derived neural stem cells, labeling of cells with various contrast agents did not affect the differentiation potential into various types of neural precursor cells.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…We did not observe any substantial differences in differentiation potential between labeled and non-labeled cells. This is in agreement with previous results on the differentiation of labeled cells in human ventral mesencephalic cells, 31 human fetal midbrainderived neural precursor, 37 SPIO-labeled human neural stem cells 28 and human fetal neural precursor cells. 45 Similarly, in iPSC-derived neural stem cells, labeling of cells with various contrast agents did not affect the differentiation potential into various types of neural precursor cells.…”
supporting
confidence: 93%
“…23,24 Comparable labeling efficiencies were shown in the labeling of neural stem cells with various types of contrast agents. [28][29][30][31] Further, we confirmed the internalization of both types of contrast agents in cell cytoplasm using TEM. Nanoparticles were present in cytoplasm in clusters surrounded by a membrane.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…In fact, several recent studies have demonstrated the efficient tracking of superparamagnetic iron oxide (SPIO)-labeled NSCs in animal models. [10][11][12][13] Nevertheless, the effects of SPIO labeling on NSC behavior and fate are not fully understood. For eventual clinical use, first, an ideal SPIO agent must not only support the uniform and long-term labeling of NSCs but also exhibit nontoxic qualities such that the intrinsic biology and function of the NSCs (which is of essence in the success of any transplantation approach) is not altered.…”
mentioning
confidence: 99%